Evaluation of chemical composition, fibre fractions and carbohydrate and protein partitioning of paddy straw, Guinea grass, and hybrid Napier (CO5) - Lasna Sahib; K. Ally; K.S Ajith; Biju Chacko; G. Radhika; K.S. Anil (Journal of Veterinary and Animal Sciences, 2025)
The nutritional evaluation of fodder resources is essential for optimising ruminant feeding strategies. This study assessed the chemical composition, fibre fractions and CNCPS (Cornell Net Carbohydrate and Protein System) carbohydrate and protein partitioning of paddy straw, Guinea grass and Hybrid Napier (CO5). Four samples of each fodder were analysed for dry matter, crude protein, ether extract, ash, neutral detergent fibre, acid detergent fibre, lignin, starch, buffer soluble protein, non-protein nitrogen, neutral detergent insoluble protein, and acid detergent insoluble protein. Carbohydrates were fractioned into CA (soluble), CB1 (starchpectins), CB2 (available fibre), and CC (unavailable fibre), while proteins were partitioned into PA (NPN), PB1 (rapidly degradable), PB2 (intermediately degradable), PB3 (slowly degradable) and PC (undegradable). Structural carbohydrates constituted the major portion, with CB2 as the predominant fraction across all fodders (P0.021). The CB1 fraction varied significantly (P0.015), with higher levels observed in Hybrid Napier and paddy straw. Protein fractionation revealed significant differences, with paddy straw exhibiting the highest PB1 fraction (P0.001), Hybrid Napier the highest PB2 fraction (P